2021
DOI: 10.15252/embj.2020107270
|View full text |Cite
|
Sign up to set email alerts
|

Paraspeckles are constructed as block copolymer micelles

Abstract: Paraspeckles are constructed by NEAT1_2 architectural long noncoding RNAs. Their characteristic cylindrical shapes, with highly ordered internal organization, distinguish them from typical liquid-liquid phase-separated condensates. We experimentally and theoretically investigated how the shape and organization of paraspeckles are determined. We identified the NEAT1_2 RNA domains responsible for shell localization of the NEAT1_2 ends, which determine the characteristic internal organization. Using the soft matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 85 publications
6
69
0
Order By: Relevance
“…In the two main steps of paraspeckle formation, first, DBHS proteins, including NONO, bind and stabilise NEAT1 lncRNA. Secondly, FUS binds and carries out phase separation dependent on its prion-like domain (Yamazaki, Yamamoto et al, 2021). Whilst a role for NONO-driven phase separation in paraspeckle formation is yet to be established, NONO phase separation is required for radiation-induced DNA damage repair (Fan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the two main steps of paraspeckle formation, first, DBHS proteins, including NONO, bind and stabilise NEAT1 lncRNA. Secondly, FUS binds and carries out phase separation dependent on its prion-like domain (Yamazaki, Yamamoto et al, 2021). Whilst a role for NONO-driven phase separation in paraspeckle formation is yet to be established, NONO phase separation is required for radiation-induced DNA damage repair (Fan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study employing polymer physics proposed a model for the organization of paraspeckles, another core-shell-type nuclear body. The report showed that parts of the building domains of the scaffold molecules (long non-coding RNAs) are mutually repulsive when positioned at the surface of paraspeckle, which accordingly determines the dynamics (size, number, and distribution) of the nuclear body; however, these repulsive domains are not required for the assembly of paraspeckle itself ( Yamazaki et al, 2021 ). Notably, SUMOylation is dispensable for the formation of PML-NBs ( Sahin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…[107] Paraspeckles resemble block copolymer micelles driven by differences in hydrophilicity along the NEAT1 chain. [108] Similarly, the lncRNA Xist, along with its protein interactome, forms compartments around the X chromosome, leading to its compaction and subsequent inactivation, potentially via phase separation. [109,110] These observations suggest that the cell harnesses the inherent separation of DNA and RNA for various functions.…”
Section: Separating the Genome From Its Rna Products: Removing Rna Fr...mentioning
confidence: 99%